Autolysis-resistant peptidoglycan of anomalous composition in amino-acid-starved Escherichia coli. - Tuomanen, E (1988)
Nongrowing Escherichia coli deprived of an essential amino acid continued to produce peptidoglycan at a rate approximately 30% of that of growing cells. The composition of this peptidoglycan was very different from that of growing cells and resembled that of peptidoglycan left undegraded during partial autolysis of the bacteria. Synthesis of this peptidoglycan of anomalous composition began at once upon the removal of the amino acid from the medium. Fifteen minutes of amino acid deprivation was sufficient to virtually completely prevent penicillin-induced autolytic wall degradation in vivo. During this time, although the specific activities of soluble and membrane-bound hydrolytic transglycosylases and endopeptidases remained high, the peptidoglycan produced showed decreased sensitivity to degradation in vitro. After more extensive (2-h) starvation, triggering of autolysis by chaotropic agents was also blocked. Autolysis in growing cells may be selective for peptidoglycan representing the cylindrical portion of the sacculus. It is suggested that at least part of the mechanism of the well-known lysis resistance of nongrowing E. coli is related to the deposition of structurally anomalous and relatively autolysin-resistant peptidoglycan at some strategically located sites on the bacterial surface.